"Reach for the sky": modeling the impact of policy stringency on industrial dynamics in the case of the REACH regulation. (28th December 2017) - Brouillat, Eric; Saint Jean, Maïder; Arfaoui, Nabila
Abstract: An agent-based model is developed as an explorative tool to investigate how the REACH regulation can help bring safer substitutes to the market. An illustration is given with the case of bisphenol-A used in food packaging. The modeling exercise enables an analysis of long-term effects of REACH on innovation and industrial dynamics caused by misfits likely to emerge between objective and perceived stringency of regulation as well as misfits related to divergent perceptions between suppliers and clients.